Demographic transition and its consequences - Lee, Ronald Demos 1941-; Reher, David Sven; Population Council (New York Population Council, 2011)
"The chapters explore the consequences of the demographic transition--characterized by low mortality and low fertility--in modern industrial societies and emerging economies. Aside from its immediate effect on population aging, the transition has implications for family and kinship patterns, public finance, the welfare state, and intergenerational relations"--Provided by publisher.
"Population and development review, a supplement to volume 37, 2011."
Keywords: Demographic transition; Population aging